2001
DOI: 10.1590/s0004-282x2001000500010
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone decreases migraine recurrence observed after treatment with a triptan combined with a nonsteroidal anti-inflammatory drug

Abstract: -Background and objectives: Triptans are effective drugs for the acute treatment of migraine. However, 30-40% of the patients commonly present recurrence before 24 hours therefore requiring another dose. Nonsteroidal anti-inflammatory drugs (NSAID) such as tolfenamic acid and naproxen sodium combined with sumatriptan have demonstrated efficacy in reducing recurrence observed with the single use of this drug. Steroids also have been suggested to treat refractory migraine and status migranosus. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…11,12,[14][15][16][17][18] In 1986, Gallagher 20 published the first clinical trial with a control arm that supported the use of dexamethasone in the ED. In this trial of 130 patients, those receiving adjunctive dexamethasone therapy had a significantly lower rate of moderate or severe headache at 24 hours compared to the control group (28% vs. 71%, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,[14][15][16][17][18] In 1986, Gallagher 20 published the first clinical trial with a control arm that supported the use of dexamethasone in the ED. In this trial of 130 patients, those receiving adjunctive dexamethasone therapy had a significantly lower rate of moderate or severe headache at 24 hours compared to the control group (28% vs. 71%, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Uncontrolled clinical trials have shown that, in both the inpatient setting and the outpatient clinic setting, dexamethasone is highly effective in reducing the severity of migraine headache and the rate of headache recurrence. [11][12][13][14][15][16][17][18][19] Although initial controlled clinical trials demonstrated the same high-level of efficacy, [20][21][22][23][24][25][26] the results of several recent ED-based trials have questioned the utility of dexamethasone for this purpose. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] The goals of this systematic review were to critically appraise the existing literature and to provide recommendations for patient care regarding the use of dexamethasone for the prevention of headache relapse in patients with acute migraine headache in the ED.…”
mentioning
confidence: 99%
“…In selected patients, triptans may be associated to other medications, in order to address specific issues, such as incomplete relieve, recurrence, or slow onset of action [71][72][73] .…”
Section: Differentiating the Triptansmentioning
confidence: 99%
“…The proposal of also using dexamethasone in a limited population of migraineurs still presenting with headache recurrence after combined treatment of a triptan with an NSAID, such as naproxen sodium or tolfenamic acid, should be considered with caution. The usefulness of this approach needs to be confirmed, as in previous clinical experiences, by case-control studies and studies with a randomized double-blind design [11]. With the affinity of triptans for 5-HT1F receptors, it is hypothetically possible that they could be a further potential target in acute migraine.…”
Section: New Insights In Triptan Researchmentioning
confidence: 91%